2017
DOI: 10.1016/j.amepre.2017.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Text4baby Influenza Messaging and Influenza Vaccination Among Pregnant Women

Abstract: IntroductionPregnant women are at risk for severe influenza-related complications; however, only 52% reported receiving an influenza vaccination during the 2013–2014 influenza season. Text4baby, a free national text service, provides influenza vaccination education and reminders to pregnant women. This study examined reported influenza vaccination during pregnancy among Text4baby participants who reported receiving influenza messages and women who reported never participating in Text4baby.MethodsOpt-in Interne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 8 publications
(10 reference statements)
0
39
0
Order By: Relevance
“…Although the use of interactive technology to engage participants is not novel, SAGE is among the first to develop and test a text messaging strategy via a CBPR process to augment parent engagement newsletters, prompting parents to interact with their preschooler about classroom activities [102][103][104]. Relying on the voice of the community whom we serve to understand what kind of information they wanted and needed to help with effective parenting about health behaviors has great intuitive potency, but is rarely used in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of interactive technology to engage participants is not novel, SAGE is among the first to develop and test a text messaging strategy via a CBPR process to augment parent engagement newsletters, prompting parents to interact with their preschooler about classroom activities [102][103][104]. Relying on the voice of the community whom we serve to understand what kind of information they wanted and needed to help with effective parenting about health behaviors has great intuitive potency, but is rarely used in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 13 studies that included a pregnant woman-centered educational component, half saw an improvement in influenza vaccine uptake among the population in the study [25,26,27,28,29,30,31]. The format of the educational materials varied.…”
Section: Risk Appraisalmentioning
confidence: 99%
“…The format of the educational materials varied. In some cases educational material about the risk of disease was written -either delivered via text message along with vaccine reminders [25,28] or as educational paragraphs or pamphlets [26,27,30,32]. In others the material was deliver orally -in one study educational videos were displayed in the waiting room [31] and in another, the educational component was an in-person session [29].…”
Section: Risk Appraisalmentioning
confidence: 99%
“…14 In fact, several studies looking at barriers and facilitators to the maternal influenza vaccine demonstrate that knowledge was a key determining factor in vaccine uptake. [15][16][17] Other research has shown that there is a relationship between maternal vaccine hesitancy, intention to vaccinate, and maternal and child vaccine rates. 18 Maternal knowledge, attitudes, and beliefs therefore should be considered not only by policy implementers and researchers alike, but prioritized as a key potential barrier when considering current and future maternal immunizations.…”
Section: Known Drivers To Vaccine Uptakementioning
confidence: 99%